Tuning the dissolution kinetics of wollastonite via chelating agents for CO2 sequestration with integrated synthesis of precipitated calcium carbonates - Zhao, Huangjing; Park, Youngjune; Lee, Dong Hyun; Park, Ah-Hyung Alissa (Physical chemistry chemical physics : PCCP, 2013)
Carbon mineralization has recently received much attention as one of the most promising options for CO2 sequestration. The engineered weathering of silicate minerals as a means of permanent carbon storage has unique advantages such as the abundance of naturally occurring calcium and magnesium-bearing minerals and the formation of environmentally-benign and geologically stable solids via a thermodynamically favored carbonation reaction. However, several challenges need to be overcome to successfully deploy carbon mineralization on a large scale. In particular, the acceleration of the rate-limiting mineral dissolution step along with process optimization is essential to ensure the economic feasibility of the proposed carbon storage technology. In this study, the effect of various types of chelating agents on the dissolution rate of calcium-bearing silicate mineral, wollastonite, was explored to accelerate its weathering rate. It was found that chelating agents such as acetic acid and gluconic acid significantly improved the dissolution kinetics of wollastonite even at a much diluted concentration of 0.006 M by complexing with calcium in the mineral matrix. Calcium extracted from wollastonite was then reacted with a carbonate solution to form precipitated calcium carbonate (PCC), while tuning the particle size and the morphological structure of PCC to mimic commercially available PCC-based filler materials.